POETIC IMAGERY AND HUMAN EXPERIENCE IN M.J. IUPPA'S STORY "SECONDHAND" - Kulmuhamedova Lobar Anvarjonovna (International Journal of Literature and Language Studies, 2026)
This article examines MJ.Iuppa’s “Secondhand” through a poetic analysis. The story reveals the inner feelings, aspirations, and emotional states of the character through depictions of everyday life. The study focuses on the use of visual imagery, metaphors, and the representation of the character’s inner world. Through simple everyday situations, the author successfully conveys deep human emotions. As a result, the significance of poetic expression and artistic devices in portraying daily life is highlighted.